Estudo comparativo da suportabilidade dielétrica de isolantes sólidos a base de celulose e aramida para aplicação em transformadores de potência - Contri, Marcelo Weber (2024)
Power transformers play a fundamental role in the electrical power system, ensuring continuity of electrical energy supply. The quality of your insulation system is a critical factor, as it directly influences the continuous operation of the transformer, as well as its cost. Traditionally, transformers used solid cellulose and mineral oil insulation, but the thermal limitations of these materials motivated the search for alternatives. Aramid-based high-temperature synthetic materials gained prominence, surpassing cellulosic insulation. In this context, this study presents a series of dielectric tests conducted in a laboratory environment, using DuPont’s Nomex® 910 and Nomex® 994 PSB, immersed in natural ester (NE) and mineral oil (OM). Two test methodologies were adopted: Creep Breakdown (CB), which evaluates electrical stresses in insulating cylinders and insulation outputs due to distorted electrical fields, and Turn-to-turn (T2T), which analyzes the electrical stress existing between turns and adjacent coil discs. The application of test voltages followed ASTM D3426, related to standardized atmospheric impulses, and ASTM D149, related to AC voltage rise. The statistical analysis of the data was based on the Weibull distribution, allowing for a comparison between the studied synthetic insulators and the traditional thermally stabilized kraft paper (TUK). The breakdown test results confirmed that the dielectric strength of TUK in EN is comparable to that in OM. Similar behavior was observed for the Nomex® 910 insulator, whose interactions between the paper/oil interfaces are distinct from those of TUK. In both methodologies, the breakdowns of Nomex® were more violent, releasing a considerable amount of suspended residues into the oil. Overall, even though aramid-based insulators exhibit superior thermal characteristics, their dielectric performances did not demonstrate competitive advantages. This, combined with the higher cost, becomes a barrier to the adoption of these materials on a large scale.